2018
DOI: 10.17977/um006v2i12018p001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Self-Adjustment on Academic Achievement of the Students

Abstract: The purposes of this research is to discover the impact of self-adjustment on student academic achievement. The method that used in this study is a correlational study with random sampling. The subject of the research is Timorese student is studying in Indonesia, there are 180 samples. The data collection has used a scale of Likert. The date is analyzed with simple correlation. The result showed there is 46.1% of significant and positive correlation of self-adjustment on student academic achievement. It means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
(12 reference statements)
0
5
0
2
Order By: Relevance
“…The results showed that the t-test (t-test) the use of concrete teaching aids significantly affected the learning outcomes of students with a t-count of 8.019 > t-table of 1.997. The t-test results appear in t-count (8,137) > t-table (1,997), then the alternative hypothesis (Ha) is accepted and Ho was rejected. This fact proves that there is a positive and significant influence between the use of figure and student learning outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results showed that the t-test (t-test) the use of concrete teaching aids significantly affected the learning outcomes of students with a t-count of 8.019 > t-table of 1.997. The t-test results appear in t-count (8,137) > t-table (1,997), then the alternative hypothesis (Ha) is accepted and Ho was rejected. This fact proves that there is a positive and significant influence between the use of figure and student learning outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…Timor Leste is a newly independent country in Century 21.As a new country, the Timorese Government needs to qualify Human Resources (HR) to build the nation [1]. Here, to get the qualified people to obtain through adequate education curriculum and system.…”
Section: Introductionmentioning
confidence: 99%
“…Dengan perolehan kontribusi kemampuan verbal terhadap prestasi belajar matematika sebesar 23,62%. Selanjutnya penelitian oleh Costa, Hanurawan, Atmoko, & Hitipeuw (2018) menyimpulkan bahwa if self-adjustment of the Timorese student was implementing well, it will elevate and increase their academic achievement. Artinya jika penyesuaian diri siswa Timor-Leste baik, maka akan berpengaruh dan meningkatnya prestasi akademik siswa.…”
Section: Pendahuluanunclassified
“…Self-adjustment is an individual's ability to understand and take certain actions as well as get acclimatized to the group's expectations (da Costa et al, 2018;Japar, 2014;Li et al, 2017;Noviandari & Mursidi, 2019). Meanwhile, good self-adjustment is the ability to manage oneself while facing these changes quickly.…”
Section: Introductionmentioning
confidence: 99%